An analysis of the impact of skilled migration on the current and future economic well-being of W.A. - Stromback, Thorsten; Mahendran, Anusha (Society of Heterodox Economists, 2008)
The presence of skill shortages has been the dominant rationale for the recruitment of trained foreign workers. Most Australian states have thus embraced the opportunities that the expansion and devolution of Australia's immigration program in recent times has given them. This paper examines the issue more closely by providing a conceptual overview of the economic case for the continuing need for skilled workers from abroad and discusses various related factors and considerations of relevance. Reference is also made to the current immigration policy and recent trends in skilled and business migration. This provides the context for a review of the contemporary economic impact that skilled migration has had in W.A and its likely future effects on the state. The anticipated future needs as indicated by the demand for skilled workers, the extent to which this demand is met by the resident workforce and the migration planning levels is also analysed.